Success of an Inpatient Rehabilitation Program in Subjects with Type 2 Diabetes Mellitus with or Without Metabolic Syndrome - Bettina Thauerer; Anna Odrovicsné Tóth; Andreas Salzer; Bibiane Steinecker-Frohnwieser (Biomolecules)
Introduction: Type 2 diabetes mellitus (T2DM) comprises heterogeneous disorders, which have an increase in blood glucose concentrations in common. Metabolic syndrome (MetS) describes the simultaneous occurrence of several clinical symptoms that increase the risk of cardiovascular disease and T2DM, although T2DM itself is also considered a risk factor for developing MetS. Objective: This study aimed to identify parameters related to rehabilitation success and relevant to MetS in T2DM patients. Methods: T2DM patients were divided into two subgroups based on the NHLBI/AHA and IDF guidelines for characterizing MetS. Serum samples were analyzed for T2DM-specific parameters, lipid metabolism, oxidative processes, AGE activity (AAct), and uric acid to HDL ratio (UHR) at admission and discharge after a 3-week inpatient rehabilitation stay. Logistic regression and before–after comparisons were performed showing the importance of multidisciplinary rehabilitation. Results: Among eighty-six patients, 59.3% had MetS. Significant differences between subgroups were found in fasting glucose (FBS), hemoglobin A1c (HbA1c), high-density lipoprotein cholesterol (HDL), triglycerides (TGLs), soluble receptor for AGE (sRAGE), UHR, and AAct. Rehabilitation-induced changes in disease-related parameters were influenced by the presence of MetS. The predictive capacity from all parameters together could be reduced within the three weeks. Conclusion: Rehabilitative measures have a major influence on MetS-relevant factors and can change the course of the disease in patients with T2DM. Identifying these factors can be of great importance for future diagnoses and treatments of T2DM and MetS.